IMPLEMENTASI PROGRAM TAHFIDZ AL-QUR’AN DI SDIT ANNAJAH BEKASI: ANALISIS TANTANGAN PEMBELAJARAN TANPA PENGUATAN TAJWID - Syifa Azqia; Afifah Octaviani; Alyaa Luthfi Nuur Haniifah; Budianto (STIT Hidayatunnajah Bekasi, 2025)
This study aims to analyze the implementation of the Qur’anic tahfidz program and the challenges of tahfidz learning without tajwid reinforcement at SDIT Annajah Bekasi. The study is based on the importance of recitation quality in tahfidz learning, while some students still experience errors in pronunciation despite good memorization achievement. This research used a qualitative approach with a case study method. Data were collected through observation, interviews, and documentation. The findings show that the tahfidz program was implemented through halaqah and talaqqi methods adjusted to students’ grade levels and cognitive development. However, challenges were found in students’ recitation quality, especially in applying tajwid rules, pronunciation accuracy of makhraj, and articulation of similar hijaiyah letters. The novelty of this study lies in its focus on tahfidz learning without structured tajwid reinforcement in Islamic elementary schools. The study concludes that tajwid reinforcement is important to balance memorization achievement and accurate Qur’anic recitation.